INDENPENSI DOKTER DALAM MEMBERIKAN RESEP OBAT KEPADA PASIEN DIKAITKAN DENGAN KODE ETIK KEDOKTERAN BERDASARKAN SURAT KEPUTUSAN PENGURUS BESAR IKATAN DOKTER INDONESIA NO.221/PB/A.4/04/2002 TENTANG PENARAPAN KODE ETIK KEDOKTERAN INDONESIA (Studi Di Rumah Sakit Umum Daerah Landak) - NPM. A2021161037, FLORENTINA MERRY, S.Farm. (Jurnal NESTOR Magister Hukum, 2018)
ABSTRACT This thesis discusses the Indentpension of Doctors in Prescribing Drug Prescriptions to Patients Associated with Medical Code of Ethics Based on the Decree of the Executive Board of the Indonesian Doctors Association No.221 / Pb / A.4 / 04/2002 on the Cause of the Indonesian Medical Code of Ethics (Study at General Hospital Landak Region). The conclusion of this thesis that the factors that cause so that doctors in prescribing drugs to patients affected or influenced by the pharmacy companies as follows Financial Interest Factors The existence of collusion of doctors and pharmaceutical companies to be the cause of the high price of drugs in this country. Research and Development Agency (Balibang) - The Ministry of Health of the Republic of Indonesia and World Health Organization (WHO) point out that the high price of medicines in Indonesia is 200 times the price of medicines in the world market and the factor of doctor's collusion with pharmaceutical companies, from observation, intention, the notion of collusion comes not just from pharmaceutical companies. Sometimes at the doctor's request. Pharmaceutical companies produce branded drugs (patents) for sale. While doctors have the authority to determine drugs. That way the pharmaceutical companies interested in the drugs are sold. The legal consequences of a physician who is directly or indirectly influenced by the pharmacy company in prescribing the drug to the patient, when seeing a doctor, certainly hope is healing. The patient does not know what the illness is, as the patient also does not know the right drug choice for the patient's healing. So the patient comes to see a doctor, because the doctor who can diagnose the disease and choose the medicine. In that relationship the patient fully surrenders the choice of medicine for the patient's healing to the doctor, who then writes the prescription. But unknowingly, once the patient comes to see a doctor, there are other interests outside the relationship of patients and doctors. Pharmaceutical companies expect how doctors who check you prescribe their production drugs. The medicine prescribed by the doctor then the patient redeemed it to the pharmacy. Efforts made by the Indonesian Doctors Association of physicians prescribing medicines to patients on the influence of pharmacy companies ie Dropping Code violations against doctors prescribing medicines to patients on the influence of pharmacy companies Medical ethics is a set of behavior of members of the medical profession in relation to clients / patients, peers and the general public and is part of the overall decision-making process and medic actions in terms of moral norms / values. And to supervise the doctor of RSUD Landak Indonesian Doctors Association (IDI) asserted, for doctors to deliberately sell or direct the patient to redeem the drug in the designated place, it violates the rules.